Transient regression of an intracranial germ cell tumour after intravenous steroid administration: a case report. Issue 5 (1st May 1998) - Mascalchi, Mario; Roncaroli, Federico; Salvi, Fabrizio; Frank, Giorgio
Abstract : Magnetic resonance imaging showed transient regression of the lesion after intravenous steroid administration in a patient with intracranial multifocal germ cell tumour. Prominent lymphocyte infiltration of the tumour was seen at histological examination and presumably accounts for the regression. Germ cell tumour must be included in the differential diagnosis of intracranial mass lesions sensitive to steroids.